ANALISIS KONTRIBUSI TENAGA KERJA PADA USAHATANI PADI LADANG DI KAMPUNG GUEINTUY DISTRIK WARMARE KABUPATEN MANOKWARI - Simanungkalit, Saut (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2024)
This research aims: 1. to find out the work potential of members of farmer households; 2. to analyze the amount of work of members of farmer households for farming; 3. to analyze the labor contribution of members of farmer households to farming. The analytical tools used in this research are analysis of job potential, workforce and workforce contribution. This research was conducted in Gueintuy Village, Warmare District, Manokwari Regency with the consideration that this area is a rice farming center area in Manokwari Regency. The data used in this research comes from primary and secondary data. Primary data was obtained from direct interviews with 30 respondents, in this case farmers who carry out field rice farming, according to the list of questions that have been prepared. Meanwhile, secondary data was obtained from related agencies, such as the Central Statistics Agency, and Agriculture Service. The results show that the average remaining household work potential of respondents in Gueintuy Village was 480,194 HKP per planting season. The employment potential obtained comes from male, female and child labor. The average amount of work in rice farming in Gueintuy Village is 48,806 HKP, consisting of the average amount of work for men of 20,493 HKP, the average amount of work for women of 20,554 HKP and the average amount of work for children of 7,759 HKP. The contribution of male, female, and child labors for rice farming in Gueintuy Village were 6.831%, 13.346%, and 10.345% respectively.